ABO incompatibility in newborn babies - Hameed, Numan N.; Jehad, Hanaa N.; Salih, Afrah A. (Journal of the Faculty of Medicine Baghdad, 2012)
Bacjground: hemolytic disease of the newborn due to ABO icompatibility (HDN-ABO) is the most common cause of hemolytic disease of the newborn.